Are doctors feeling burnout? – Multicenter cross-sectional study on burnout syndrome and its determinants during the ongoing pandemic - Ashutosh Kumar; Kavita Chawla; Arun Mishra; Geetu Singh; Achyut K. Pandey; Praveen Rikhari (Indian Journal of Psychiatry)
Background: Though the concept of burnout has been around for long, its significance is increasing nowadays owing to the demanding nature of jobs. The latest ICD-11 also provides a detailed description of Burnout syndrome. Physicians are at high risk for experiencing burnout and this becomes especially relevant in the ongoing COVID-19 pandemic. Aim: To determine the risk of burnout among medical faculty and its predictors, if any. Materials and Methods: This was a multicentric cross-sectional study that included medical faculty from four tertiary care government teaching hospitals in north India. A survey was conducted during the current COVID-19 pandemic to assess burnout using a structured online questionnaire based on Burnout Assessment Tool. The questionnaire also included relevant socio-demographic, professional, health, and lifestyle-related details. Descriptive statistics, Mann-Whitney U Test/Kruskal Wallis Test, and Kendall’s tau-b Test were used for statistical analysis. Results: A total of 244 medical faculty completed the survey. 27.87% were at risk of burnout, out of which 11.89% were at a very high risk of burnout. Dissatisfaction with the job and dissatisfaction with sleep (P < 0.01 for both) were associated with greater burnout scores and a greater risk of burnout. Conclusion: Faculty members are at high risk of burnout, regardless of sociodemographic and work-related factors.